2021
DOI: 10.2147/clep.s310795
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Assisted Reproduction in Women with a Wide Spectrum of Chronic Diseases – A Review

Abstract: Assisted reproductive technology (ART) treatments in women with underlying chronic diseases have become increasingly frequent. The objective of this review is to provide an overview of the literature examining the chance of having a live born child after ART in women with chronic diseases, compared to other women receiving ART. We focused on some of the most prevalent chronic diseases in women during their reproductive years, ie ulcerative colitis, Crohn’s disease, rheumatoid arthritis, multiple sclerosis, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 96 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…A metanalysis of 13 papers looking at ART in people with chronic illness, with several papers considering people with epilepsy (PWE), suggested people with chronic illness had an equivalent chance of a live birth compared to those without a chronic disease. 2 Another study showed that the chance of a live birth per embryo transfer was similar in people with and without epilepsy, demonstrating the efficacy of infertility treatment in PWE. Thus, PWE seeking fertility therapy should be reassured that several studies have demonstrated that anti-seizure medications (ASMs) use during ART treatment did not significantly affect the chances of live birth after embryo transfer nor was there a difference in time to pregnancy.…”
Section: Commentarymentioning
confidence: 98%
“…A metanalysis of 13 papers looking at ART in people with chronic illness, with several papers considering people with epilepsy (PWE), suggested people with chronic illness had an equivalent chance of a live birth compared to those without a chronic disease. 2 Another study showed that the chance of a live birth per embryo transfer was similar in people with and without epilepsy, demonstrating the efficacy of infertility treatment in PWE. Thus, PWE seeking fertility therapy should be reassured that several studies have demonstrated that anti-seizure medications (ASMs) use during ART treatment did not significantly affect the chances of live birth after embryo transfer nor was there a difference in time to pregnancy.…”
Section: Commentarymentioning
confidence: 98%